(untitled) (UBS Scientific Bulletin, 2025)
The article examines the different approaches to identifying the key components of human capital and the main sources from which human capital accumulates. It studies a wide range of literature related to the basic components of human capital, sources of human capital formation in order to identify the common aspects, and generalize the ideas. The author analyzes education, health, training, migration and information as the main sources of human capital, and proposes that abilities, knowledge, skills and personality constitutes the human capital.